2015
DOI: 10.3390/antib4040279
|View full text |Cite
|
Sign up to set email alerts
|

B Cell Help by CD1d-Rectricted NKT Cells

Abstract: B cell activation and antibody production against foreign antigens is a central step of host defense. This is achieved via highly regulated multi-phase processes that involve a variety of cells of both innate and adaptive arms of the immune system. MHC class II-restricted CD4 + T cells specific for peptide antigens, which acquire professional follicular B cell helper functions, have been long recognized as key players in this process. Recent data, however, challenge this paradigm by showing the existence of ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…iNKT cells are a subset of innate-like T cells that expresses semiinvariant TCR (12,13) and recognizes lipid Ags presented by CD1d molecules (14). It has been reported that iNKT cells could provide help to B cells directly or indirectly (15,16). During indirect help, iNKT cells promote the maturation of dendritic cells (DCs) through cognate interactions, and educated DCs enhance the development of T FH cells (17,18).…”
mentioning
confidence: 99%
“…iNKT cells are a subset of innate-like T cells that expresses semiinvariant TCR (12,13) and recognizes lipid Ags presented by CD1d molecules (14). It has been reported that iNKT cells could provide help to B cells directly or indirectly (15,16). During indirect help, iNKT cells promote the maturation of dendritic cells (DCs) through cognate interactions, and educated DCs enhance the development of T FH cells (17,18).…”
mentioning
confidence: 99%
“…In order to produce IgG antibodies, B cells require the cooperation of a T cell subset that expresses CD40L and produces class-switching cytokines, such as IL-4 or IFN-γ. NKT cells are lymphocytes restricted to the recognition of lipid antigens presented by CD1d molecules [ 20 ], and could provide the cooperation required to produce the IgG anti-NPA antibodies detected in C57BL/6 mice that received NPA-bearing liposomes. Here we evaluated the number of NK1.1 + , CD4 + T cells and their activation in C57BL/6 mice that produce anti-NPA antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…NKT cells respond rapidly to antigenic stimulation by secreting IL-4 and IFN-γ, which results in the activation of numerous immune cells, including dendritic cells, NK cells, B cells and CD4 + and CD8 + T cells [24]. NKT cells interact through their TCR with CD1dexpressing B cells, and this interaction leads to B cell proliferation and antibody production, and to increased NKT cell activation [20,21,25]. This cooperation requires the expression of CD40 on B cells and of CD40L on NKT cells; likewise, it needs the production of IL-4 and antibodies against lipid antigens [20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations